Soroprevalência de Rickettsia spp. em equídeos e pesquisa de Rickettsia spp. em carrapatos Amblyomma cajennense e Dermacentor nitens da região do Pantanal mato-grossense, Brasil - Alves, Alvair da Silva (2014)
The aim of the study was to estimate the rickettsial (Rickettsia rickettsii, Rickettsia parkeri, ‘Candidatus R. amblyommii’, Rickettsia rhipicephali, and Rickettsia bellii) infection in equids, and ticks of a Pantanal region of Brazil. Sera of 547 equids (500 horses and 47 mules, and donkeys) were evaluated by indirect immunofluorescence assay (IFA). A total of 665 adults and 106 nymphal pools of Amblyomma cajennense F. s.l., 10 Dermacentor nitens Neumann ticks, and 88 larval pools of Amblyomma sp. were tested by PCR. Overall 337 (61.6%) equids were reactive (titer ≥ 64) to at least one antigen of Rickettsia spp. The prevalence values for Rickettsia were 66%, and the highest endpoint titers were observed for ‘Ca. R. amblyommii’. In PCR 3 (0.45%) female of A. cajennense s.l. were positive for ‘Ca. R. amblyommii’. For the immature ticks were observed a minimum rate of infection of 0.75% and 0.34 % for nymphs and larvae, respectively. Positive samples of ticks have had a fragment of the 16S mitochondrial rRNA gene sequenced and sequences showed 99% similarity to Amblyomma sculptum Berlese. This study reports a wide distribution of Rickettsia among equids, suggesting the possible involvement, for the first time, of A. sculptum in transmitting ‘Ca. R. amblyommii’.